Suppressed charge carrier trap states and double photon absorption in substitutional Ta-doped TiO2-NT array. (April 2022) - Huai, Xiaochen; Rizzi, Gian Andrea; Wang, Yanfeng; Qi, Qige; Granozzi, Gaetano; Fu, Wangyang; Zhang, Zhengjun
Highlights: Research highlights item 1: We revealed the mechanism of Ta substitution in TiO2 -NTs for suppressing the charge carrier trap states and double-photon absorption. Research highlights item 2: We introduced Ta to substitute Ti position in TiO2 -NTs lattice through a simple fluorination process. Research highlights item 3: We excited the photogenerated carriers under a modulated sinusoidal visible light to simulate the kinetics of charge carriers at the ETL/PAL interface. Graphical Abstract: ga1 Abstract: Anatase-TiO2 nanotubes (A-TiO2 NTs) represent a great opportunity for the electron transport materials used in perovskite solar cells because of several intrinsic advantages, e.g. an improved light trapping effect, an inherent ion-blocking layer, a directed electron transmission channel without interfacial random scattering. Nevertheless, its severe double-photon absorption and charge carrier trap states badly jeopardize the stability and electron transport of the perovskite active layers (PALs) under visible light, representing a major obstacle for practical applications. In this paper, we introduce Ta to substitute Ti position in A-TiO2 NTs lattice through a simple fluorination process, and reveal its underneath mechanism on suppresing the abovementioned limiting factors of charge carrier trap states and double-photon absorption. Moreover, we use the effect of double-photon absorption of studied NTs to excite the photogenerated carriers under a modulated sinusoidal visible light with small amplitude, which can perturb the transport dynamics of photo-induced charge carriers and simulate the dynamic process of charge carriers at the interface between electron transport layer (ETL) and PALs in real time. These achievements highlight the unique potential of substitutional Ta doping for interfacing engineering of perovskite solar cells.